2014
DOI: 10.1113/jphysiol.2013.267294
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic control of vascular tone in the retina

Abstract: Key pointsr The blood supply to the CNS is controlled by the tone of arteries and arterioles. However, little is known about purinergic regulation of vascular tone in the CNS.r We have investigated purinergic control of vascular tone in the in vivo rat retina. r Reducing endogenous ATP levels by enzyme degradation and inhibiting purinergic signalling with P2X receptor antagonists decreases the tone of retinal arterioles. Raising ATP levels increases vessel tone.r Experiments using fluorocitrate to poison the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 59 publications
(83 reference statements)
2
50
0
Order By: Relevance
“…Fluorocitrate could also be acting on neurons or on vascular cells to reduce vessel tone. This is unlikely, however, as the toxin is believed to act selectively on glial cells and reduces vascular tone in the retina by decreasing stimulation of P2 receptors [13]. The tonic release of ATP from Mü ller cells could also modulate the excitability of retinal neurons, for instance, inhibiting the firing of RGCs.…”
Section: Tonic Release Of Atp From Glial Cells Generates Vascular Tonementioning
confidence: 99%
See 3 more Smart Citations
“…Fluorocitrate could also be acting on neurons or on vascular cells to reduce vessel tone. This is unlikely, however, as the toxin is believed to act selectively on glial cells and reduces vascular tone in the retina by decreasing stimulation of P2 receptors [13]. The tonic release of ATP from Mü ller cells could also modulate the excitability of retinal neurons, for instance, inhibiting the firing of RGCs.…”
Section: Tonic Release Of Atp From Glial Cells Generates Vascular Tonementioning
confidence: 99%
“…We have found that tonic release of ATP from glial cells could be responsible for generating tone in retinal arterioles [13]. Manipulation of endogenous ATP levels results in large changes in vascular tone.…”
Section: Tonic Release Of Atp From Glial Cells Generates Vascular Tonementioning
confidence: 99%
See 2 more Smart Citations
“…Rather than triggering a rapid vascular response, synaptic activity-evoked astrocyte calcium increases have been proposed to mediate sustained vascular responses to prolonged stimulation [40,43,44]. Furthermore, astrocytes also appear to play a role in maintaining the resting tone of the vasculature [45][46][47], which could affect the size of the blood flow response following neuronal activity [48].…”
Section: Cellular Mechanisms Underlying Bold: How Our Incomplete Undementioning
confidence: 99%